(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we provide an upper bound for the intersection number in the join and corona of graphs. Moreover, we give formulas for the intersection number of Kn ◦G, Pn ◦G, Cn ◦G and Crn.